آدابِ نعت گوئی ونعت خوانی کے لوازم - Razi, Muhammad Naqeeb Ullah (Zoraiz, 2022)
Naat is a charming style of rendering flowers of devotion and love in the court of last prophet Hazrat Muhammad Mustafa (PBUH). Its two forms are very important. One is Naat writing, which is related to the creation of Naatiya verses and the other is Naat recitation, which is related to the presentation of Naat with rhythm, pleasant tone and musicality. Above mentioned both types have their own manners. Many Naat poets and Naat reciters do not take care of these manners and instead of getting virtues, it becomes a source of sin for them. In this paper, such manners have been highlighted in the light of Quran, Hadith and Islamic teachings so that the sacredness of this genre may be maintained and purity can be developed in the creation and recitation of Naat.